Identification of Potential Interaction Networks Using Sequence-Based Searches for Conserved Protein-Protein Interactions or “Interologs” - Matthews, Lisa R.; Vaglio, Philippe; Reboul, Jérôme; Ge, Hui; Davis, Brian P.; Garrels, James; Vincent, Sylvie; Vidal, Marc (Genome Research, 2001)
Protein interaction maps have provided insight into the relationships among the predicted proteins of model organisms for which a genome sequence is available. These maps have been useful in generating potential interaction networks, which have confirmed the existence of known complexes and pathways and have suggested the existence of new complexes and or crosstalk between previously unlinked pathways. However, the generation of such maps is costly and labor intensive. Here, we investigate the extent to which a protein interaction map generated in one species can be used to predict interactions in another species.
10.1101/gr.205301